Peers, neighborhoods and immigrant student achievement: Evidence from a placement policy - Olof Åslund; Per-Anders Edin; Peter Fredriksson; Hans Grönqvist (Institute for Labour Market Policy Evaluation (IFAU), 2009)
Immigrants typically perform worse than other students in the OECD countries. We examine to what extent this is due to the population characteristics of the neighborhoods that immigrants grow up in. We address this issue using a governmental refugee placement policy which provides exogenous variation in the initial place of residence in Sweden. The main result is that, for a given share of immigrants in a neighborhood, immigrant school performance is increasing in the number of highly educated adults sharing the subject's ethnicity. A standard deviation increase in the fraction of highly educated adults in the assigned neighborhood increases compulsory school GPA by 0.9 percentile ranks. This magnitude corresponds to a tenth of the gap in student performance between refugee immigrant and native-born children. We also provide tentative evidence that the overall share of immigrants in the neighborhood has a negative effect on GPA.
Keywords: I20; J15; Z13; 330; Peer effects; ethnic enclaves; immigration; school performance; Migranten; Segregation; Bildungsniveau; Allgemeinbildende Schule; Bildungsverhalten; Schweden